Management systems and soil quality in soybean production in the low altitude closure (Research, Society and Development, 2020)
The objective was to evaluate the physical and chemical attributes of a OXISOL of clayey texture and the phytotechnical parameters of the soybean crop. The experiment was conducted at the Teaching, Research and Extension Farm of UNESP, Ilha Solteira Campus. The experimental design was a randomized block design, with 7 treatments and 4 replications, being: aiveca plow, minimum cultivation, heavy grating, consolidated no - tillage, no - tillage planted on aiveca plow, no - tillage planted on minimum tillage and no - tillage planted on heavy grid. The physical and chemical attributes of the soil, plant height and first pod insertion, shoot diameter, number of grains per pod, mass of 1000 grains, dry mass of plants, productivity and initial and final stand were evaluated of soy. There was statistical difference in the layer of 0.00-0.10m for soil chemical attributes, the consolidated no-tillage system presented better results. In the layers of 0.10-0.20 and 0.20-0.30m, the highest values of potassium were obtained with soil stirring. The highest penetration resistance was observed in the layer of 0.20-0.30 m in the preparation systems that were subjected to stirring.The first pod insertion height was higher in the heavy grating system.